Pendampingan Pemanfaatan Buku Amalan Harian Santri dalam Meningkatkan Spiritualitas dan Moral Santri - Muhammad Almeyda El Jalaluddin Rumi; Suci Midsyahri Azizah (Social Science Academic, 2025)
This study aims to develop a book using the Asset Based Community Development (ABCD) approach. This method emphasizes the use of community assets and potentials in the book-making process. The stages include: (1) Discovery, identifying community assets and skills; (2) Dream, formulating shared expectations about the book; (3) Design, arranging the content and structure of the book; and (4) Destiny, realizing the design into a published book. The results show that the use of the ABCD approach increases community participation, makes the book content more contextual to local needs, and fosters a sense of ownership of the final product. Therefore, the ABCD method can be an effective approach in community-based book development. Due to the tradition of the students reading daily practices (Discovery) but the students can only imitate the imam's reading sometimes the majority of the students do not memorize the reading of the practice I hope (Dream) with the existence of this book of daily practices of students the students not only listen but they can imitate the reading by reading the practice book, Where this practice book is designed (Design) as neat and simple as possible so that the students not only read the book when reading the daily practice but the students can also memorize the contents of the practice book, With this book, I hope that the students of the Nurul Qur'an Islamic Boarding School are able to follow the reading of the practice read by the Imam and maybe the students are also able to easily memorize daily practices, such as reading Tahlil, Yasin, Al-Mulk, Asror and other prayers, And my hope as a devotee of this practice book is not only useful for the students but is useful and sustainable (Define) with income or image (Citra) from the next pondok printing business and maybe other books will be published if this daily practice book of students is successful in penetrating the general market.